Potensi Pemberdayaan Tanah Wakaf dalam Penyelenggaraan Perumahan - Muhammad Mahdi (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Housing problems are an issue that always arises, especially in developing countries. The high demand is not proportional to the supply and ability to provide decent housing. In Indonesia there are around 800 thousand new households every year that need decent housing, while the housing backlog is still at 12-15 million. This article discusses the potential utilization of waqf land for housing provision. This article was written based on literature study. The findings in this article are, there is great potential for utilizing waqf land in Indonesia. First, the number of waqf land in Indonesia is spread across 440,512 locations with an area of 57,263.69 hectares. Second, most of the use of waqf land is still consumptive. The presence of the government to make waqf land more productive is very important and highly anticipated.